2018
DOI: 10.1002/pca.2801
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvent as a green solvent for enhanced extraction of narirutin, naringin, hesperidin and neohesperidin from Aurantii Fructus

Abstract: Introduction In the present study, a green and efficient extraction method using deep eutectic solvents as extraction solvent was developed for extracting the four major active compounds narirutin, naringin, hesperidin and neohesperidin from Aurantii Fructus. Methodology A series of tunable deep eutectic solvents were prepared and investigated by mixing choline chloride or betaine to different hydrogen‐bond donors, and betaine/ethanediol was found to be the most suitable extraction solvent. To achieve the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…For solvent to feed ratios below 300, only reduced yields were achieved. Several authors also reported a dependency of extraction yield on solvent to feed ratio . Similarly, they found that an increase of solvent to feed ratio generally leads to an increase of the yield of the target compound.…”
Section: Resultsmentioning
confidence: 88%
“…For solvent to feed ratios below 300, only reduced yields were achieved. Several authors also reported a dependency of extraction yield on solvent to feed ratio . Similarly, they found that an increase of solvent to feed ratio generally leads to an increase of the yield of the target compound.…”
Section: Resultsmentioning
confidence: 88%
“…The chosen extraction parameters were 50 • C, 20% H 2 O content and 30 min. The extraction time of 30 minutes and extraction temperature was chosen according to our own experience, as well as according to Liu et al [17] who have shown that 30 min was the optimal time to extract hesperidin. Water content is important for reducing viscosity, but very high water content reduces the interaction between components, therefore, 20% (v/v) of water was selected.…”
Section: Screening Of Des For Hesperidin Extractionmentioning
confidence: 99%
“…When mixed in a certain ratio and depending on the type of used HBD and HBA, DESs with desirable properties are produced [15]. Recently, DESs are being used for the extraction of flavonoids from various fruits, vegetables and spices [16], as well as from Citrus aurantium L. [17] and the orange (Citrus sinensis) peels [18] where the DESs composition, concentration of added water, solid-to-liquid ratio and the effect of time, temperature and stirring speed on the extraction yield and composition of extracted flavonoids have been investigated. According to the results, DESs showed higher extraction yields and an increase in the solubility of active constituents compared to the other traditional solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, DESs possess the same favourable properties as ILs, including negligible volatility at room temperature, wide liquid range, tunable viscosity, superior thermal stability and designable structures . Additionally, DESs are considered superior to ILs for the properties of biodegradability, environmental friendliness and lower costs for preparation, and have been used in various chemistry fields, including catalysis, organic chemistry, electrochemistry, analytical chemistry, and extraction processes of chemical compounds …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Additionally, DESs are considered superior to ILs for the properties of biodegradability, environmental friendliness and lower costs for preparation, and have been used in various chemistry fields, including catalysis, organic chemistry, electrochemistry, analytical chemistry, and extraction processes of chemical compounds. [9][10][11][12][13][14][15][16][17][18][19][20] The Epimedium herb, Yinyanghuo in Chinese, is a famous Chinese herbal medicine. In the 2015 version of Pharmacopoeia of the People's Republic of China, "Yinyanghuo" were identified as the dried leaves of E. brevicornu Maxim., E. sagittatum (Sieb.…”
Section: Introductionmentioning
confidence: 99%